2017
DOI: 10.15249/11-1-143
|View full text |Cite
|
Sign up to set email alerts
|

Responsible business practices: Aspects influencing decision-making in small, medium and micro-sized enterprises

Abstract: Society demands responsible business practices (RBP) from all businesses, including small, medium and micro-sized enterprises (SMMEs). The conscious decision to partake in RBP resides with the main decision-makers of SMMEs. This article identifies which aspects influence the decision-makers of SMMEs to utilise business resources for RBP, and the different demographic variables that impact on these influencing aspects.Responses from 84 SMMEs indicate that the company's current financial condition is the greates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…corporate social responsibility [CSR]/SR) are represented by members of specific societies, on one hand, and how they are incorporated within existing frames knowledge and cultural practices, on the other. Second, we uncover other non-philanthropic practices that constitute the wider RBPs in microbusinesses-understood in line with the definition of Cronje et al (2017). This definition of RBPs is synonymous with the essence of (C)SR in the academic literature (see Dahlsrud, 2008), which enables us to explore SR-related issues using a concept (RBP) that is non-limiting as in the Nigerian context where SR is synonymous with philanthropy.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…corporate social responsibility [CSR]/SR) are represented by members of specific societies, on one hand, and how they are incorporated within existing frames knowledge and cultural practices, on the other. Second, we uncover other non-philanthropic practices that constitute the wider RBPs in microbusinesses-understood in line with the definition of Cronje et al (2017). This definition of RBPs is synonymous with the essence of (C)SR in the academic literature (see Dahlsrud, 2008), which enables us to explore SR-related issues using a concept (RBP) that is non-limiting as in the Nigerian context where SR is synonymous with philanthropy.…”
mentioning
confidence: 82%
“…Previous studies have reported the motivations for small business owner‐managers to engage in RBPs (Cronje et al, 2017) and the aspects that affect their decision making with regard to RBPs (Dincer & Dincer, 2013; Lepoutre & Heene, 2006; Moore & Spence, 2006; Wong & Bustami, 2020). Findings from those studies suggest that SMEs have specific characteristics that distinguish them from larger businesses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Responsible Business Practices and concern for sustainability in order to protect the Environment is hardly one of the top priorities of SMEs. Company's current financial condition is the greatest influence for SMEs to utilize business resources for Responsible Business Practices while ethics only influences to a moderate extent (Cronje, 2017). The social responsibility of the Managers in the SME will play a significant role and has a positive impact on the SME business (Pletnev, 2016).…”
Section: Business Factorsmentioning
confidence: 99%